States and power in Africa Comparative lessons in authority and control - Herbst, Jeffrey (Princeton, 2000)
Theories of international relations, assumed to be universally applicable, have failed to explain the creation of states in Africa. There, the interaction of power and space is dramatically different from what occurred in Europe. In his ground-breaking book, Jeffrey Herbst places the African state-building process in a truly comparative perspective, examining the problem of state consolidation from the precolonial period, through the short but intense interlude of European colonialism, to the modern era of independent states. Herbst's bold contention - that the conditions now facing African state-builders existed long before European penetration of the continent - is sure to provoke controversy, for it runs counter to the prevailing assumption that colonialism changed everything. In identifying how the African state-building process differs from the European experience, Herbst addresses the fundamental problem confronting African leaders: how to extend authority over sparsely settled lands. Indeed, efforts to exert control over vast, inhospitable territories of low population density and varied environmental and geographical zones have resulted in devastating wars, millions of refugees, and dysfunctional governments perpetrating destructive policies. Detailing the precise political calculations of distinct African leaders, Herbst isolates the basic dynamics of African state development. In analyzing how these leaders have attempted to consolidate power, he is able to evaluate a variety of policy alternatives for dealing with the fundamental political challenges facing African states today.
Keywords: Africa-Politics and government